1997
DOI: 10.1121/1.418242
|View full text |Cite
|
Sign up to set email alerts
|

Sonoluminescence: An alternative “electrohydrodynamic” hypothesis

Abstract: A mechanism is proposed for the sonoluminescence (SL) arising from a single bubble maintained in levitation by an acoustic field. This proposal follows from a plasma diagnostic analysis which reveals that a single Ar bubble is characterized by a sparklike plasma (electron temperature and density: 20 000 K and 1025 m−3, respectively). The theoretical scenario (based on four hypotheses) is as follows. During its expansion and the major part of its collapse, a levitating bubble is governed by Rayleigh–Plesset dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…However, there was little agreement as to the details of how this worked, and many other physical mechanisms were suggested, including dielectric breakdown of the gas (Garcia and Levanyuk, 1996;Lepoint et al, 1997;Garcia and Hasmy, 1998), fracture-induced light emission (Prosperetti, 1997), bremsstrahlung (Moss, 1997;Frommhold, 1998), collision-induced emission (Frommhold and Atchley, 1994;Frommhold, 1997;Frommhold and Meyer, 1997), and even the quantum-electrodynamical Casimir effect (Eberlein, 1996a(Eberlein, , 1996b, an idea pioneered in this context by Schwinger (1992).…”
Section: Historical Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was little agreement as to the details of how this worked, and many other physical mechanisms were suggested, including dielectric breakdown of the gas (Garcia and Levanyuk, 1996;Lepoint et al, 1997;Garcia and Hasmy, 1998), fracture-induced light emission (Prosperetti, 1997), bremsstrahlung (Moss, 1997;Frommhold, 1998), collision-induced emission (Frommhold and Atchley, 1994;Frommhold, 1997;Frommhold and Meyer, 1997), and even the quantum-electrodynamical Casimir effect (Eberlein, 1996a(Eberlein, , 1996b, an idea pioneered in this context by Schwinger (1992).…”
Section: Historical Overviewmentioning
confidence: 99%
“…In this vein, another attempt at an electrical breakdown model was made by Garcia et al (1999). Earlier, Lepoint et al (1997) speculated on sparklike discharges around water jets invading a bubble. Prosperetti (1997) also invoked an electrical mechanism for light emission (fractoluminescence) as a byproduct of a fluid-mechanical picture of sonoluminescence light emission that requires asymmetric collapse of the bubble.…”
Section: B Sbsl: a Multitude Of Theoriesmentioning
confidence: 99%
“…Lepoint et al [135] observed that the spectra of single argon bubbles are similar to that of capillary spark discharges. Such discharges were previously shown to be associated with electron temperatures of 20 000-30 000 K and plasma densities of up to 10 26 electrons per m 3 [136,137].…”
Section: Other 'Hot-spot' Modelsmentioning
confidence: 89%
“…Several nanoseconds before maximum collapse the bubble interface becomes unstable and needle-like, energetic jets propagate into the bubble interior more or less isotropically, giving rise to separation of electrical charge and subsequent spark-like discharges. While the various aspects and hypotheses necessary for that mechanism to work are developed with care [135], it will be diYcult to combine this model with the hydrodynamic equations to demonstrate the necessary quantitative agreement with measurements. In any case, remarkably similar temperature and electron density estimates have been advanced in other recent work; see section 2.4.2 above.…”
Section: Other 'Hot-spot' Modelsmentioning
confidence: 99%
“…In [68], the light source is assumed to be spark discharges around a water jet; in [69], the source is assumed to be electric discharges in cracks formed in water as a result of con tact between a gas jet and the bubble wall. The authors of [70,71] assume that photons are mainly emitted by atoms of noble gases dissolved in water according to the following scenario.…”
Section: Electric Modelsmentioning
confidence: 99%